2014
DOI: 10.1038/mp.2013.189
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive development in 22q11.2 deletion syndrome: comparison with youth having developmental delay and medical comorbidities

Abstract: The 22q11.2 deletion syndrome (22q11DS) presents with medical and neuropsychiatric manifestations including neurocognitive deficits. Quantitative neurobehavioral measures linked to brain circuitry can help elucidate genetic mechanisms contributing to deficits. To establish the neurocognitive profile and neurocognitive “growth charts”, we compared cross-sectionally 137 individuals with 22q11DS ages 8–21 to 439 demographically matched non-deleted individuals with developmental delay (DD) and medical comorbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 56 publications
10
95
1
1
Order By: Relevance
“…Thus, learning difficulties are very common in preschool and primary school, especially within the domains of mathematics (De Smedt et al, 2009a, 2009b; Tobia, Brigstocke, Hulme, & Snowling, 2017; Wang, Woodin, Kreps-Falk, & Moss, 2000) and language comprehension (Glaser et al, 2002; Van den Heuvel et al, 2016). Cognitive deficits are seen in the majority (90–100%) of individuals with 22q11DS with impairments in sustained attention, executive function, memory, and visual-spatial perception (Antshel, Fremont, & Kates, 2008; Campbell & Swillen, 2005; Gur et al, 2014). In a recent cross-sectional study (Gur et al, 2014), the cognitive functions of 137 subjects (aged 8–21) were compared with youth with a developmental delay and medical comorbidities and with typically developing controls.…”
Section: Cognitive Development In 22q112 Dsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, learning difficulties are very common in preschool and primary school, especially within the domains of mathematics (De Smedt et al, 2009a, 2009b; Tobia, Brigstocke, Hulme, & Snowling, 2017; Wang, Woodin, Kreps-Falk, & Moss, 2000) and language comprehension (Glaser et al, 2002; Van den Heuvel et al, 2016). Cognitive deficits are seen in the majority (90–100%) of individuals with 22q11DS with impairments in sustained attention, executive function, memory, and visual-spatial perception (Antshel, Fremont, & Kates, 2008; Campbell & Swillen, 2005; Gur et al, 2014). In a recent cross-sectional study (Gur et al, 2014), the cognitive functions of 137 subjects (aged 8–21) were compared with youth with a developmental delay and medical comorbidities and with typically developing controls.…”
Section: Cognitive Development In 22q112 Dsmentioning
confidence: 99%
“…Cognitive deficits are seen in the majority (90–100%) of individuals with 22q11DS with impairments in sustained attention, executive function, memory, and visual-spatial perception (Antshel, Fremont, & Kates, 2008; Campbell & Swillen, 2005; Gur et al, 2014). In a recent cross-sectional study (Gur et al, 2014), the cognitive functions of 137 subjects (aged 8–21) were compared with youth with a developmental delay and medical comorbidities and with typically developing controls. Greatest deficits were observed in the domains of complex cognition (verbal language-mediated reasoning, non-verbal reasoning, and spatial processing).…”
Section: Cognitive Development In 22q112 Dsmentioning
confidence: 99%
“…5,6 The associated phenotype is variable and can include neuropsychiatric and physical features, with cardiac, palate, endocrine, and immunologic abnormalities. 5,79 Psychiatric disorders are common, affecting three quarters of individuals with 22q11DS; there is increased risk for autism, attention-deficit/hyperactivity disorder (ADHD), anxiety disorders, and, most notably, psychosis. 1015 Approximately a third of individuals with 22q11DS develop psychotic disorders by adulthood, representing a 25-fold increase in psychosis risk over the general population, and 10-fold over other developmentally delayed populations.…”
Section: Introductionmentioning
confidence: 99%
“…The 22q11.2DS is also one of the highest known risk factors for the development of schizophrenia; 30%-40% of adults with this syndrome meet diagnostic criteria for a schizophrenia spectrum disorder (Schneider et al, 2014a). In the past decade, a large number of studies have described the cognitive profile of people with 22q11.2DS and have notably shown that executive functioning is a particular weakness (Campbell et al, 2010;Gur et al, 2014;Niklasson & Gillberg, 2010;Shapiro, Wong, & Simon, 2013). For example, Campbell et al (2010) observed that children with 22q11.2DS have impaired planning abilities and limited cognitive flexibility.…”
mentioning
confidence: 99%